PENGARUH MEDIA AUDIO-VISUAL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE KANCING GEMERINCING (TALKING CHIPS) - Ida Marlina; Arwin Achmad; Rini Rita T. Marpaung (Universitas Lampung, 2013)
Observation on 7th grade at Junior High School of 5th Bandar Lampung reveals that the critical thinking ability and the material mastery were not optimal due to teacher-centered oriented learning. Therefore it is necessary to develop media and learning model study. To resolve it, the research using audio-visual media and talking chips model was conducted. The research design that used in this research is pre-test post-test non-equivalent. Samples used are 7 D and 7F class chosen by cluster random sampling method. Quantitative data obtained from pretest and posttest scores and N-gain which analyzed using t-test. Qualitative data gained from questionnaire regarding student response on audio-visual media through talking chips model which analyzed descriptively. Result of the research reveals that the average of critical thinking skill and material mastery of subject matter of the experimental class on all indicators (critical thinking skills N-gain 26,79%, material mastery N- gain 28,46%). Moreover, 87.50% students give positive response on audio-visual media through talking chips learning model. Therefore, the using of audio-visual media through talking chips has a positive influence significant on increasing the critical thinking skill and material mastery of the student. Keywords: audio-visual media, talking chips, critical thinking skill, material mastery.